Cohesion and coherence of EFL students’ essay writing - Riswanto, Riswanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study analyzed cohesion and coherence in students' essay writing in terms of (1) the types of cohesion and coherence used by students and (2) students' awareness of creating cohesion and coherence by utilizing the descriptive qualitative method. Research population was fifth semester Tadris Bahasa Inggris (TBI) students at UIN FAS Bengkulu. As a research sample, the technique of purposive sampling was used. As the subject, 29 TBI 5E students were investigated. Data were collected from an old document including essays written by students. The results were qualitatively examined using Halliday and Hasan's theory of cohesiveness, and the absolute scale served as the foundation for Bachman and Palmer's coherence rating scale. In addition, this current study results showed that students used the Halliday and Hasan coding scheme, the types of references used are R11, R12, R13, R14, R21, R22, R23, R31, R32, R33, and R34, and the types of conjunction used are C111, C121, C141, C142, C151, C152, C212, C213, C22, C232, C241, C311, C322, C351, C411, C42, C431, C445, C451, C452, C461, C481, and C5 and the types of reiteration used are L1, L2, L3, and L4. Then, students' ability to build cohesion was referenced 52.1% of the time, while conjunction was used 40.8% of the time. It was then followed by a 7.2% reiteration. Furthermore, students' ability to build coherence was on the Extensive Scale (3) and the Complete Scale (4) on average. It indicates that students have a sufficient understanding of how to construct coherence in their writing. The study's findings indicate cohesion and coherence must be emphasized in writing instruction also English teachers must be adequate in evaluating the cohesion and coherence of students' writing to improve.